Environmental impacts of war’s social consequences. Case Study: Aleppo Governorate Syria - Papadimitriou, Kyriaki; Koumoulidis, Dimitrios; Papalamprou, Lida; Kasimatis, Christoforos-Nikitas; Sparangis, Panagiotis; Katsenios, Nikolaos; Vlachakis, Dimitrios; Triantakonstantis, Dimitris; Efthimiadou, Aspasia (My University, 2021)
War is an anthropogenic phenomenon with devastating effects, which cause loss of human life, alongside the disastrous effects on the natural environment. The environmental impacts of armed conflicts can be either direct, arising from the act of war itself, or indirect due to the massive population displacement, infrastructure breakdown, and militarised zones. Impacts may be irreversible, affecting areas even far away from the territory of the conflict where they manifest. The environmental impacts of war create social and economic consequences that lead to greater environmental degradation by showing the interdependent relationship between the environment, society, and economy. It is imperative to address the subject in a multidisciplinary approach and implement stricter international legislation on environmental disasters during wars. This study aims to identify environmental impacts by using satellite-derived images at Aleppo Governorate, analyse them via statistics supplemented with the available information for the research region, and demonstrate the subsequent social and economic consequences by creating indices, such as the Normalised Difference Vegetation Index (NDVI), digital image composites and classified images, which record the extent of reduction of healthy vegetation and the extent of destruction at the city of Aleppo. Data from international organisations corroborated the findings, and hereinafter societal and economic effects were analysed. Using remote sensing alongside with geographic information systems can be a useful tool as it offers access to war zones where physical observations are usually impossible.
Keywords: Environmental impacts; Armed conflicts; Remote sensing; Geographic information system; Syria; Aleppo Governorate